2023
DOI: 10.3389/fpubh.2023.1224143
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the effect of photoplethysmograms on workers’ exposure to methyl bromide using second derivative

Jungmi Choi,
Wonseok Cha,
Min-Goo Park

Abstract: Methyl bromide (MB) is worldwide the only effective fumigant heavily used for quarantine pre-shipment treatment and has a critical use exemption for soil fumigations due to its excellent permeability and insecticidal effect. However, MB should be replaced as it is an an ozone-depleting substance and also highly toxic to humans. Recently, MB has been shown to be hazardous even for asymptomatic workers, affecting their central and autonomic nervous systems. However, the effects of MB exposure on vascular health … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 38 publications
(60 reference statements)
0
1
0
Order By: Relevance
“…MB was classified as an ozone-depleting substance under the Montreal Protocol, which was established in 1989 [ 10 ], and the International Plant Protection Organization (IPPC) recommended its replacement and reduction [ 11 ]. Furthermore, MB is a highly toxic pesticide, and recent studies have reported that, even without obvious symptoms, workers experience negative effects in relation to their central nervous, autonomic nervous, and vascular systems [ 12 , 13 , 14 ]. Korea has developed MB alternatives such as phosphine (PH 3 ) and ethyl formate (EF), which have been used in quarantine procedures since 2011, and ethanedinitrile (EDN), which was introduced in 2019 [ 15 , 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…MB was classified as an ozone-depleting substance under the Montreal Protocol, which was established in 1989 [ 10 ], and the International Plant Protection Organization (IPPC) recommended its replacement and reduction [ 11 ]. Furthermore, MB is a highly toxic pesticide, and recent studies have reported that, even without obvious symptoms, workers experience negative effects in relation to their central nervous, autonomic nervous, and vascular systems [ 12 , 13 , 14 ]. Korea has developed MB alternatives such as phosphine (PH 3 ) and ethyl formate (EF), which have been used in quarantine procedures since 2011, and ethanedinitrile (EDN), which was introduced in 2019 [ 15 , 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, there has been a need for frequent fumigation with methyl bromide (MB) in these countries [ 7 ]. However, MB negatively impacts the value of the produce [ 8 ] and the health of the workers [ 9 , 10 , 11 ], making it necessary to replace MB with safer fumigants. Moreover, when passion fruits are exported, the pests in the fruits must be controlled before export.…”
Section: Introductionmentioning
confidence: 99%